Ureteral Injury with Delayed Massive Hematuria after Transvaginal Ultrasound-Guided Oocyte Retrieval - Tanja Burnik Papler; Eda Vrtačnik Bokal; Vesna Šalamun; Dejan Galič; Tomaž Smrkolj; Nina Jančar (Hindawi Limited, 2015)
We report a case of ureteral injury with delayed hematuria after transvaginal oocyte retrieval. A 28-year-old infertile patient with a history of previous laparoscopic resection of endometriotic nodes of both sacrouterine ligaments presented with abdominal pain one day after oocyte retrieval. Four days after oocyte retrieval, she presented with massive hematuria that reappeared 6 days after oocyte retrieval. Monopolar coagulation with wire electrode and insertion of a double-J-stent was performed during operative cystoscopy. The patient recovered completely after transfusion and had no signs of renal impairment after ureteric stent removal. This is the first report of ureteral injury after oocyte retrieval presenting itself with delayed massive hematuria and no signs of renal dysfunction or urinary leakage into retroperitoneal space.